Synthesis of gold nanoparticles with Solanum xanthocarpum extract and their in vitro anticancer potential on nasopharyngeal carcinoma cells - Zhang P (Dove Medical Press, 2018)
Pengfei Zhang,1,* Peicheng Wang,2,* Lei Yan,3 Lifeng Liu1 1Department of Otolaryngology – Head and Neck Surgery, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi 710061, China; 2Department of Otolaryngology – Head and Neck Surgery, Weihai Municipal Hospital, Weihai, Shandong 264200, China; 3Innoscience Research Sdn. Bhd, Subang Jaya, Selangor 47500, Malaysia *These authors contributed equally to this work Background: Nasopharyngeal cancer (NPC) is one of the subtypes of head and neck cancers. It occurs rarely, and its prevalence depends mainly on geographical location. Modern-day research is focused on coupling nanotechnology and traditional medicine for combating cancers. Gold nanoparticles (AuNPs) were synthesized from Solanum xanthocarpum (Sx) leaf extract using reduction method. Methods: Characterization of the synthesized AuNPs was done by different techniques such as ultraviolet–visible spectrum absorption, X-ray diffraction, dynamic light scattering, Fourier transform infrared spectroscopy, transmission electron microscopy, and energy-dispersive X-ray analysis. Results: All the results showed the successful green synthesis of AuNPs from Sx, which induced apoptosis of C666-1 cell line (NPC cell line). There was a decline in both cell viability and colony formation in C666-1 cells upon treatment with Sx-AuNPs. The cell death was proved to be caused by autophagy and mitochondrial-dependent apoptotic pathway. Conclusion: Thus, due to their anticancer potential, these nanoparticles coupled with Sx can be used for in vivo applications and clinical research in future. Keywords: Solanum xanthocarpum, gold nanoparticle, C666-1 cells, ROS, apoptosis